Digital forensics and cyber crime : 11th EAI International Conference, ICDF2C 2020, Boston, MA, USA, October 15-16, 2020, Proceedings - International Conference on Digital Forensics and Cyber Crime 2020 : Online); Goel, Sanjay (Of University of Albany, SUNY); Gladyshev, Pavel; Johnson, Daryl; Pourzandi, Makan; Majumdar, Suryadipta (Cham : Springer, 2021)
This book constitutes the refereed proceedings of the 11th International Conference on Digital Forensics and Cyber Crime, ICDF2C 2020, held in Boston, MA, in October 2020. Due to COVID-19 pandemic the conference was held virtually. The 11 reviewed full papers and 4 short papers were selected from 35 submissions and are grouped in topical sections on digital forensics; cyber-physical system Forensics; event reconstruction in digital forensics; emerging topics in forensics; cybersecurity and digital forensics.
On Reliability of JA3 Hashes for Fingerprinting Mobile Applications -- Make Remote Forensic Investigations Forensic Again: Increasing the Evidential Value of Remote Forensic Investigations -- Evidence gathering in IoT criminal investigation Effective Medical Image Copy-Move Forgery Localization Based on Texture Descriptor -- A Partial Approach to Intrusion Detection -- Efficient Fingerprint Matching for Forensic Event Reconstruction -- Modelling GOP structure effects on ENF-based video forensics -- Android Dumpsys Analysis to Indicate Driver Distraction -- Adapting to local conditions: Similarities and differences in anonymous online market between Chinese and English Speaking Communities -- Remote air-gap Live forensics -- A Digital Forensic Approach for Optimizing the Investigation of Hit-And-Run Accidents -- An Intelligence Criminal Tracker for Industrial Espionage: Applying Digital Data Acquired Onsite to Target Criminals -- Retracing the Flow of the Stream: Investigating Kodi Streaming Services -- Cybersecurity Methodology for Specialized Behavior Analysis -- Neural Representation Learning Based Binary Code Authorship Attribution.
International conference proceedings.
Includes author index.
Online resource; title from PDF title page (SpringerLink, viewed March 17, 2021).
Keywords: Computer crimes -- Investigation -- Congresses; Computer security -- Congresses; Computer crimes -- Investigation; Computer security; Electronic books; Conference papers and proceedings